Funkcja nauczycielska kobiety w myśli Jana Chryzostoma - Szczur, Piotr (Vox Patrum, 2016)
The Church Fathers repeatedly spoke about the function that women should play – especially Christian women – in the communities they lived in. One of the widely discussed problems in ancient times was the question of teaching by women. It was discussed whether women in general can teach, and if so, under what circumstances? In this article I decided to investigate this issue on the basis of selected speeches of John Chrysostom. The first point of the present study notes that in ancient times the public teaching and speaking in general was a manifestation of power. The next two sections present Chrysostom’s comments on this topic based on the exegesis of biblical texts 1 Timothy 2:11-15 and Romans 16:3-16. In the final conclusions it should be underlined, that John Chrysostom firmly holds to the teaching of Scripture (especially St. Paul). He makes a distinction between private and public teaching. According to him, women can only lead private teaching activity (especially in the family), but they cannot teach in public, because such teaching is associated with the holding of an ecclesiastical office, reserved for men. A man teaches a woman, not the other way around – this is the standard situation. Reversing these roles was permitted only in exceptional circumstances.